Understanding political contestation in Malaysia - Jawan, Jayum (Institute for Southeast Asian Studies, Busan University of Foreign Studies, 2016)
This paper argues and shows how ethnic dimension is still very important in understanding political contestations in Malaysia. To do this, the paper reviews the political as well as population demography to back its assertion. And it is not necessarily improper to continue to use this ethnic lens, although the continued use of this approach has come under heavy criticism both within and from outside Malaysia. Raging debates in Malaysia and by Malaysians are still very much shaped by ethnicity and increasing regional differences. This is further compounded by other factors such as religion, language, and education. In fact, these tools have been more intensely used of late compared to any period before in history as they easily politicize and attract followers.